Acousto-optical analogue of a Fabry – Perot resonator. (January 2021) - Pustovoit, V.I.
Abstract: A new method is proposed to increase the spectral resolving power of collinear acousto-optical filters by using optical feedback when the light leaving the region of its interaction with a periodic structure formed in the crystal by an acoustic wave returns to the input of the crystal, in which the diffraction process repeats itself many times. The light beam returned to the interaction region changes the boundary conditions of the parametric diffraction problem, because of which the amplitudes of the diffracted and passed light beams turn out to be strongly dependent on the feedback properties (similar to the processes occurring in a Fabry – Perot optical resonator). It is shown that such a combined acousto-optical Fabry – Perot filter with feedback is able to electronically tune the optical transmission wavelength and simultaneously has a higher spectral resolution than a conventional acousto-optical filter without feedback. It is also shown that the multiple radiation diffraction due to the feedback increases the diffraction efficiency with a comparatively small spatial change in the refractive index of the medium. Explicit analytical expressions for the instrumental functions of a combined acousto-optical Fabry – Perot filter are found and their properties are analysed. It is noted that a change in the feedback by any mechanism, i.e., by changing the returned wave phase or amplitude, leads to modulation of the measured signal, which makes it possible to create more precise methods of spectral measurements.